2011
DOI: 10.1159/000328030
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and Nitrosative Stress Markers in Patients on Hemodialysis and Peritoneal Dialysis

Abstract: Aim: The aim of this study was to evaluate the effects of hemodialysis (HD) and peritoneal dialysis (PD) treatments on oxidative and nitrosative stress markers comparatively. Methods: Twenty HD and 20 PD patients as well as 20 healthy individuals were included in this study. Plasma advanced oxidation protein products, myeloperoxidase, thiol group and 3-nitrotyrosine (3-NT) levels were measured in all subjects. Results: Plasma advanced oxidation protein products and myeloperoxidase levels were elevated by HD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…In our results, there were significantly higher postdialysis values of native thiol, dynamic disulphide, and total thiol compared to predialysis values. There are similar studies in the literature showing the effect of hemodialysis on antioxidant homeostasis [ 10 , 24 , 26 , 29 ]. In a study conducted by Colombo et al, it was found that lower plasma levels of total thiols in patients with end-stage kidney disease compared to the healthy controls were the same as those of the healthy persons' after dialysis, and they attributed this result to hemodialysis being the first session [ 26 ].…”
Section: Discussionmentioning
confidence: 67%
“…In our results, there were significantly higher postdialysis values of native thiol, dynamic disulphide, and total thiol compared to predialysis values. There are similar studies in the literature showing the effect of hemodialysis on antioxidant homeostasis [ 10 , 24 , 26 , 29 ]. In a study conducted by Colombo et al, it was found that lower plasma levels of total thiols in patients with end-stage kidney disease compared to the healthy controls were the same as those of the healthy persons' after dialysis, and they attributed this result to hemodialysis being the first session [ 26 ].…”
Section: Discussionmentioning
confidence: 67%
“…Increased mitochondrial production of ROS may activate proinflammatory pathways and affect the structure of lipids and proteins and enzyme activity [15]. Although four different pathways of oxidative stress probably take place in CKD, literature data suggest that nitrosative and carbonyl stress plays a crucial role here [11, 16]. Therefore, uremia may be characterized as carbonyl overload or “carbonyl stress” which reflects increasing oxidation of proteins, carbohydrates, and lipids and no effective detoxification or complications associated with chronic renal failure and dialysis [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification of the risk factors for the development and progression of CVD has never been overstated. Much evidence suggests that chronic renal failure patients under regular dialysis treatment have increased oxidative stress 21,22 . Exposure of proteins to reactive oxygen results in modification of amino acid residues, subsequently damaging proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence suggests that chronic renal failure patients under regular dialysis treatment have increased oxidative stress. 21,22 Exposure of proteins to reactive oxygen results in modification of amino acid residues, subsequently damaging proteins. Our and other previous studies have shown that oxidized serum proteins are not only a marker of oxidative stress, but also a contributor to atherosclerotic and other complications seen in patients with end stage renal disease.…”
Section: Discussionmentioning
confidence: 99%